Assessing levels and trends of adult mortality in Sub Saharan Africa using INDEPTH health and demographic surveillance systems - (:unkn) unknown (My University, 2017)
There is still a considerable dearth of knowledge regarding adult mortality and premature deaths in Sub-Saharan Africa (SSA). Attempts to measure adult mortality using censuses and cross-sectional surveys rely mainly on indirect techniques that are affected by common biases. The growing number of Health and Demographic Surveillance Systems (HDSSs) offer a mediumterm solution to the dearth of knowledge regarding adult mortality and the main causes in Africa. This paper compares adult mortality estimates from 16 HDSSs in nine countries in SSA based on publicly available data on INDEPTHStats. We use Life Table techniques to examine differences in adult mortality trends and to identify mortality clusters and sex differentials. Results reveal distinctive mortality trends for the three regions of Africa with the Southern and Eastern African regions having relatively higher mortality than the West African region.
Keywords: African Research